Dark‐State Induced Quantum Nonreciprocity. Issue 3 (28th January 2022) - Nefedkin, Nikita; Cotrufo, Michele; Krasnok, Alex; Alù, Andrea
Abstract: With the development of quantum technologies and their broad applications, the phenomenon of reciprocity breaking has been evolving from an effective tool in classical wave optics and electrodynamics to a promising instrument also for the field of quantum computing and quantum information processing. In this work, nonreciprocal wave phenomena that arise in atom‐like quantum systems are studied. Different approaches to isolation and nonreciprocity in quantum systems are reviewed, with a focus on a specific class of passive devices where nonreciprocity is induced by the system nonlinearity, without the need of an external bias. It is then discussed how to model these effects and what their underlying physics is, outlining how the existence of a slowly‐decaying subradiant state is critical to obtain large nonreciprocal responses. The susceptibility of these devices to changes in the environment is analyzed, together with the opportunities that come from including temporal modulations. Abstract : Quantum nonreciprocal transmission is achieved with an asymmetric pair of atoms that interact nonlinearly with light, and they are coupled to an optical waveguide. The effect is largely asymmetric transmission of light quanta in the few‐photon limit.